Epilogue: Anthropological conversations with Karl Wittfogel's ghost. (November 2019) - Strang, Veronica
This epilogue provides a 'last word' to this rich collection of papers engaging in lively dialogue with Wittfogel's ghost. It suggests that although his writing has been criticised as deterministic and generalising, with hindsight, Wittfogel is best appreciated as a scholar thinking within a particular historical and intellectual context. Part of the abiding appeal of his perspective comes from the clear and strong lines it draws connecting water, infrastructure and power.